2009
DOI: 10.1080/10673220903149135
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Meditation in Addressing Psychiatric Illness, with a Focus on Substance Use Disorders

Abstract: Over the past 30 years the practice of meditation has become increasingly popular in clinical settings. In addition to evidence-based medical uses, meditation may have psychiatric benefits. In this review, the literature on the role of meditation in addressing psychiatric issues, and specifically substance use disorders, is discussed. Each of the three meditation modalities that have been most widely studied—transcendental meditation, Buddhist meditation, and mindfulness-based meditation—is critically examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 71 publications
1
24
0
2
Order By: Relevance
“…Several theoretical review papers have hypothesized that mind–body practices such as yoga and meditation/mindfulness may be beneficial for preventing and treating substance abuse and addictive behavior (e.g., Calajoe 1987; Dakwar and Levin 2009; Kissen and Kissen-Kohn 2009; Lohman 1999). Indeed, a recent increase in research on this topic has led to a number of systematic literature reviews summarizing the effects of mind–body practices on substance use (Carim-Todd et al 2013; Chiesa and Serretti 2014; Katz and Toner 2013; Khanna and Greeson 2013; Zgierska et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical review papers have hypothesized that mind–body practices such as yoga and meditation/mindfulness may be beneficial for preventing and treating substance abuse and addictive behavior (e.g., Calajoe 1987; Dakwar and Levin 2009; Kissen and Kissen-Kohn 2009; Lohman 1999). Indeed, a recent increase in research on this topic has led to a number of systematic literature reviews summarizing the effects of mind–body practices on substance use (Carim-Todd et al 2013; Chiesa and Serretti 2014; Katz and Toner 2013; Khanna and Greeson 2013; Zgierska et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness training may be beneficial in a number of ways: by improving attention and self-awareness; by revitalizing the capacity for healthy adaptation; by ameliorating drug-related ruminations and cravings; by reducing emotional reactivity, cue reactivity and stress sensitivity; by correcting problematic cognitions; and by providing a rewarding and relaxing alternative to drug use. 1,19,20 The focus of training, especially in the individual setting, can be readily guided by the particular deficits and needs of the patient (see Case 2).…”
Section: Discussionmentioning
confidence: 99%
“…Part of the reason for the rising interest in meditation is that clinical research now suggests that meditation-based practices may be an effective means of addressing anxiety (Goldin and Gross 2010), depression (Toneatto and Nguyen 2007), and substance abuse (Dakwar and Levin 2009). Published accounts of meditation-based medical research typically focus on changes in biomarkers or self-reported scales before and after a standardized intervention.…”
Section: Introductionmentioning
confidence: 99%